Mutation detection : a practical approach - Cotton, Richard G. H.; Edkins, E. (Edward); Forrest, S. (Sue) (Practical approach series, 1998)
Mutation detection is increasingly undertaken in a wide spectrum of research areas: in medicine it is fundamental in isolating disease genes and diagnosis, and is especially important in cancer research; in biology, commercially important genes can be identified by the mutations they contain. But mutation detection is time-consuming and expensive. This volume offers tried and tested protocols for a range of detection methods, from the labs of researchers in the field.